INTERACTIVE EDUCATIONAL TECHNOLOGIES IN THE TRAINING OF A FUTURE BIOLOGY TEACHER FOR SPECIALIZED SCHOOL - Romaniuk (Melnychenko), Ruslana; Tanska, Valentyna (Professional Pedagogics, 2019)
The relevance of the study is determined by the integration of Ukraine into the European educational system, reforms of secondary education, the transition to specialized education in high school, the growing requirements to vocational training of graduates of higher education institutions, the need to change from the traditional academic style of teaching disciplines to innovation. The aim is to generalize scientific, educational-methodical sources and personal practical experience of using interactive pedagogical techniques in forming the professional competence of the Biology teacher of the specialized school. Methods used in the research include theoretical (analysis of scientific and pedagogical sources, articles, abstracts, dissertations, Internet resources; synthesis and generalization of factual material; comparison and classification) and empirical methods (pedagogical observation, questioning, interviews with students). The results. The role of interactive techniques in teacher’s training has been analyzed; it is noted that the organization of education on a competence approach is based on strengthening of practical professional orientation of education, development of students’ pedagogical abilities and values. The author has implemented the preparation of the future Biology teacher of the specialized school at the second (master’s) level of higher education while ... . Anonymous questionnaires of the master-graduates, the future teachers of Biology, Chemistry and the Fundamentals of Human Health have been conducted. The respondents have been asked to rate on a five-point scale the effectiveness of a method, a form, a teaching technique in forming their readiness to work at a specialized school. The analysis of the results of the study is carried out on the basis of ... Conclusions. Training the modern teacher of the specialized school should be carried out due to the strengthening of the practical component of educational programs. Special attention should be paid to on-the- job (pedagogical) practices in general secondary education institutions with specialized classes...